Arctic Arts with Pride: Discourses on Arctic Arts, Culture and Sustainability - Maria Huhmarniemi; Timo Jokela (Sustainability, 2020)
There has been growing interest in Arctic arts and culture as well as in sustainability among artists, researchers, and policy makers. However, until recently, the comprehension of Arctic arts and culture within the framework of sustainable development has remained vague. In this study, by analysing diverse debates from the Arctic Arts Summit 2019 in Rovaniemi, we investigate how the arts and culture sector promotes Arctic sustainability. An analysis of abstracts, conclusions, blogs and newspaper articles reflecting the presentations, art events, exhibitions and dialogues showed that the discourse on sustainability is organised around five themes: (1) global politics and ecological crises as part of the cultural politics of the Arctic; (2) indigenous and non-indigenous Arctic arts and culture; (3) ‘handmade’ and the material culture of the Arctic; (4) place-making, revitalisation and regional development; and (5) economy and sustainability. These partly interlinked themes have relevance for policy making, defining principles for arts and culture funding, artistic practice and research on the Arctic. In addition, education and artistic training are important for all of the five themes; therefore, resources for educational institutions are crucial for the sustainable future of the Arctic. Arts, culture and education have the potential to empower people in the Arctic, increase cultural pride, educate and inform global audiences and create connectedness between the past, present and future. Arts, culture and education contribute to Arctic sustainability.